2010
DOI: 10.2174/156720510790691326
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Hyperhomocysteinemia Increases Amyloid-β Formation and Deposition in a Mouse Model of Alzheimers Disease

Abstract: Hyperhomocysteinemia (HHcy) has been recognized as a risk factor for developing Alzheimer’s disease (AD). However, its underlying molecular mechanisms are still elusive. Here we show that HHcy induces an elevation of amyloid beta (Aβ) levels and deposition, as well as behavioral impairments, in a mouse model of AD-like amyloidosis, the Tg2576 mice. This elevation is not associated with significant change of the steady state levels of the Aβ precursor protein (APP), β - or α-secretase pathways, nor with the Aβ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 35 publications
(47 reference statements)
3
58
1
Order By: Relevance
“…Additionally, immunoblot analyses showed that these cells had a significant increase in tau phosphorylation at the same epitopes as for the brain tissues from the diet mice and a selective activation of the cdk5 pathway. Because recent data from transgenic mice support the hypothesis that A β can modulate cellular metabolic events leading to phosphorylation-specific changes in tau, 20 and considering that Hcy can act on A β metabolism per se, 1012 it was possible that in our study the effect on tau was secondary to that on Ab. However, based on our results we conclude that the effect of Hcy on tau phosphorylation is independent from Ab, because suppression of A β formation did not alter the Hcydependent tau phosphorylation.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Additionally, immunoblot analyses showed that these cells had a significant increase in tau phosphorylation at the same epitopes as for the brain tissues from the diet mice and a selective activation of the cdk5 pathway. Because recent data from transgenic mice support the hypothesis that A β can modulate cellular metabolic events leading to phosphorylation-specific changes in tau, 20 and considering that Hcy can act on A β metabolism per se, 1012 it was possible that in our study the effect on tau was secondary to that on Ab. However, based on our results we conclude that the effect of Hcy on tau phosphorylation is independent from Ab, because suppression of A β formation did not alter the Hcydependent tau phosphorylation.…”
Section: Discussionmentioning
confidence: 78%
“…11 Our group and others have reported that a diet low in folate, vitamin B6, and vitamin B12 produces high circulating Hcy levels and results also in an exacerbation of AD-like brain amyloidosis. 10,12 However, due to the limitations of the APP mice, which develop only 1 of the 2 major hallmark lesions of AD (ie, amyloidosis), no data are available on whether high Hcy levels also influence the development of tau neuropathology, and importantly, whether these effects are independent from each other. With this knowledge in mind, for this study we used the 3xTg mice, which develop both amyloid plaques and tau fibrillary tangles, and fed them a folate-, B6-, and B12-deficient diet, which is a well-established model to induce high levels of Hcy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations